Intelligent process automation: An overview over the future of auditing - Nunes, T. (2021)
Financial auditing focuses on obtaining and assessing evidence, based on certain assertions. It is based on the scrutiny of companies' data, with the objective of obtaining appropriate and sufficient evidence that provides a reasonable degree of certainty that the financial statements are free from fraud and / or material errors, subsequently communicating the results to the stakeholders. However, the growing dimension and complexity of organizations, well represented by the volume of data they currently generate and store, have greatly increased the requirements for the auditor's work, which must be effective and efficient. Classic audit procedures, which are highly dependent on sampling and manual procedures, have proved to be insufficient. Due to the massive amount of data, the emergence of new technologies and computer tools at a frenetic level, auditing is now being rethought, with the debate extending from professional organizations to academics. This article brings together the gaps and shortcomings recently revealed in the thought of the so-called traditional audit, and the challenges it faces today. It presents the new technologies, specifically Robotic Process Automation and Artificial Intelligence, as already having expression in today's audit, and which, in a future vision, are enhanced by their combination in Intelligent Process Automation.